Implementasi Efektivitas Supervisi Pendidikan terhadap Mutu Pendidikan - Amelia Amelia; Irma Tussa’diyah Hasibuan; Mulia Ardiansyah Harahap; Okta Elviana Manurung; Yusuf Ali Ahmad Harahap; Inom Nasution (Sublim: Jurnal Pendidikan, 2023)
This paper discusses the implementation of educational supervision to improve the quality of education. Supervision is a planned coaching activity to assist teachers and other school employees in doing their jobs effectively. In the context of education, the notion of quality includes input, process and output of education. To improve the quality of education, the role of educational supervision should not be neglected. Because supervision is a significant thing in realizing that quality. Supervisors (supervisors, school/madrasah principals) must have expertise and seriousness in supervising educational institutions in order to improve the quality of education.